(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The problem in this research is "Can the reading literacy skills of first grade students at SDN 8 Kabila Bone through image media increase? "The goal to be achieved in this study is to increase initial reading literacy through the media of pictures of first grade students at SDN 8 Kabila Bone, Bone Bolango Regency. This type of research is classroom action research (CAR), which consists of 2 cycles The results of the study showed that in the first cycle the first meeting was 10 students or 40% who were able to read initial literacy, cycle I the second meeting, namely 13 students or 52% who were able to read initial literacy, because in the first cycle they had not reached the predetermined performance indicators, they continued in cycle II. In cycle II the first meeting, namely 17 students or 68% who were able to read initial literacy and in cycle II the second meeting increased to 22 students or 88%. Students already understand and actively participate in the learning process through the media of images. Thus it can be concluded that through media images the initial reading literacy skills of grade I students at SDN 8 Kabila Bone, Bone Bolango Regency have increased